The symptoms and diagnosis of pyloric obstruction - Hamilton, Robert (The University of Edinburgh, 1909)
Diseases of the stomach form a large proportion of the cases met with in general practice. Their treatment in these circumstances is often prolonged and unsatisfactory because a thorough examination of the stomach and its functions is considered inconvenient or unnecessary, and although many accurate clinical methods are available they are too rarely employed until the disease has resulted in gross lesions of the stomach, requiring some surgical interference and perhaps beyond the possibility of cure. Many cases of pyloric obstruction of this kind have come before me, and their diagnosis has sometimes been a matter of difficulty. I propose therefore to discuss the signs, symptoms and diagnosis, first, of pyloric obstruction generally, and secondly, of each form of pyloric obstruction.